The Global Antimicrobial Resistance Epidemic - Innovative Approaches and Cutting-Edge Solutions 2022
DOI: 10.5772/intechopen.104226
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Antibiotics in Semen Extenders Used in Artificial Insemination

Abstract: Antimicrobial resistance is a serious global threat requiring a widespread response. Both veterinarians and medical doctors should restrict antibiotic usage to therapeutic use only, after determining the sensitivity of the causal organism. However, the addition of antibiotics to semen extenders for animal artificial insemination represents a hidden, non-therapeutic use of antimicrobial substances. Artificial insemination for livestock breeding is a huge global enterprise with hundreds of million sperm doses pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…It was possible to retrieve approximately 85% of the original load of boar spermatozoa using this method, and sperm quality was not adversely affected by the lack of selection for robustness . Preliminary results from an AI trial indicated that fertility was similar in control and treated samples (Morrell et al, 2022). These results suggest that a similar approach for stallion semen might be possible.…”
Section: Single Layer Centrifugation With a Low Density Colloidmentioning
confidence: 81%
“…It was possible to retrieve approximately 85% of the original load of boar spermatozoa using this method, and sperm quality was not adversely affected by the lack of selection for robustness . Preliminary results from an AI trial indicated that fertility was similar in control and treated samples (Morrell et al, 2022). These results suggest that a similar approach for stallion semen might be possible.…”
Section: Single Layer Centrifugation With a Low Density Colloidmentioning
confidence: 81%
“…Moreover, bacteria may develop resistance [ 88 ]. It is questionable whether this nontherapeutic use of antibiotics fits with current recommendations for prudent use of antimicrobial substances [ 89 ]. Most of the liquid portion of the inseminate is expelled from the uterus via backflow; thus, the bacteria in the vagina and in the environment are exposed to the antibiotics contained in the insemination dose.…”
Section: Bacterial Contaminationmentioning
confidence: 99%
“…In the latter case, a low-density colloid could be used instead of the high-density colloid needed for the selection of robust sperm. When this technique was used to prepare boar semen for AI, there was no detrimental effect on reproductive efficiency in the inseminated sows compared to controls [ 89 ].…”
Section: Bacterial Contaminationmentioning
confidence: 99%
“…Alternatives for antibiotics in semen extender have been discussed previously (Morrell et al 2022;Morrell and Wallgren 2014). Plant-based substances with known antimicrobial properties on different isolated bacteria have been proposed as an alternative but until recently, their antimicrobial effect in bull sperm had not been tested.…”
Section: Introductionmentioning
confidence: 99%